2015
DOI: 10.1007/s11468-015-0011-6
|View full text |Cite
|
Sign up to set email alerts
|

Selectively Imaging Single Gold Nanorods by Polarized Light Microscopy with Low Background

Abstract: We introduce a novel method for single gold nanorods (GNRs) imaging by polarized light microscopy (PLM) based on their light depolarization light property. The results demonstrate that GNRs can be selectively seen by PLM, while sphere gold nanoparticles only can be observed under darkfield microscopy (DFM). When PLM is applied in single nanoparticle imaging, there are many outstanding features. For example, the average light spot of GNRs occupies 71± 26 pixels, which is only 42 % of that under DFM. The backgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…To suppress background scattering, cross-polarization [30][31][32] has been highly effective at providing high-contrast imaging of plasmonic nanoprobes. In cross-polarization, a polarizer is placed in the illumination path creating linearly polarized illumination, followed by the sample specimen labeled with anisotropic plasmonic nanoprobes, and subsequently followed by another polarizer placed in the detection path aligned orthogonally with respect to the other polarizer.…”
Section: Introductionmentioning
confidence: 99%
“…To suppress background scattering, cross-polarization [30][31][32] has been highly effective at providing high-contrast imaging of plasmonic nanoprobes. In cross-polarization, a polarizer is placed in the illumination path creating linearly polarized illumination, followed by the sample specimen labeled with anisotropic plasmonic nanoprobes, and subsequently followed by another polarizer placed in the detection path aligned orthogonally with respect to the other polarizer.…”
Section: Introductionmentioning
confidence: 99%
“…Jacobson [15] has shown that AuNPs can be readily distinguished from background scatterers by using interferometric method and the wavelength dependence of plasmon resonances. Kimura et al [16] employed AFM to visualize subsurface AuNPs buried in a soft polymer matrix with a depth of 1 μm, and in a recent research, Chen et al [17] used polarized light for imaging single gold nanorods with improved Signal-to-Noise Ratio (SNR).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the asymmetric illumination of dark field microscopy, non-spherical GNR can enhance this contrast more than their spherical counterparts [14]. Their shape can also allow for visualization using cross-polarized microscopy [15]. Due to the light-scattering properties of GNR and their ability to specifically target cellular receptors [16], we believe that GNR conjugated with target specific proteins can be used to evaluate biomarker levels in a method similar to IHC.…”
Section: Introductionmentioning
confidence: 99%